The use of the Eurosystem's monetary policy instruments and its monetary policy implementation framework between the first quarter of 2018 and the fourth quarter of 2019 - Julie Sylvestre; Cristina Coutinho (European Central Bank (ECB), 2020)
This paper provides a comprehensive overview of the use of the Eurosystem's monetary policy instruments and the operational framework, from the first quarter of 2018 to the last quarter of 2019. It reviews the context of Eurosystem market operations; the design and operation of the Eurosystem's counterparty and collateral frameworks; the fulfilment of minimum reserve requirements; participation in credit operations and recourse to standing facilities; and the conduct of outright asset purchase programmes. The paper also discusses the impact of monetary policy on the Eurosystem's balance sheet, excess liquidity and money market liquidity conditions.
Keywords: D02; E43; E58; E65; G01; 330; monetary policy implementation; central bank counterparty framework; central bank collateral framework; central bank liquidity management; non-standardmonetary policy measures